Auditor Eksternal, Komite Audit, dan Manajemen Laba Sanjaya - I Putu Sugiartha Sanjaya (The Indonesian Journal of Accounting Research, 2013)
The objective of this paper is to investigate whether earnings management is different between audited and non-audited firms (big four and non big four). This study also investigates whether earnings management is different between companies forming and not forming audit committees (eligible and ineligible to Jakarta Stock Exchange (JSX)). The study investigates whether earnings management for companies forming audit committee is eligible and employ big four auditors is lower than three other groups of companies.  This study uses data of 127 manufacturing companies listed in JSX. The result of this study shows that earnings management is somewhat lower for big four than non big four auditors. But, earnings management is not different for companies forming and not forming audit committees, and employing combination between audit committee and auditor.